Identifying innovation factors and actors in autonomous inland shipping: a literature review - Dhaneswara Al Amien (Journal of Shipping and Trade, 2024)
Abstract Autonomous shipping is introduced to increase the competitiveness of inland shipping and promote a modal shift toward sustainable transport. This innovation has the potential to disrupt the existing inland shipping industry paradigm. This paper identifies the characteristics of autonomous inland shipping through the lens of the diffusion of innovation theory. A systematic literature review, based on the PRISMA 2020 guidelines methodology, was conducted. The existing literature aligns well with the theory and reveals most of the innovation variables and relevant actors. The result indicates that the literature on this topic is limited but still developing, and the paper presents opportunities for agendas in business, innovation, and transportation research. Further discussion shows industry implications, using a generalized transport cost model and stakeholder analysis to emphasize the motivations for sustainable transport through the adoption of autonomous shipping.